Use of Learning Videos as a Medium to Support Islamic Religious Education for Students hith Disabilities at SLB PGRI Dlanggu - Falahiyah, Fina; Bakr, Mohammed Abou; Saifuddin, Saifuddin; Rozi, Syaikhu (Universitas Yudharta Pasuruan, 2024)
An Extraordinary School (SLB) is an institution for children with special needs, where each child requires specific understanding and treatment. In the subject of Islamic Religious Education (PAI), worship practices are taught to students with below-average IQs. Teachers need to present the material innovatively, as lectures alone are insufficient to engage these students. This research focuses on: 1) The characteristics of students with disabilities at SLB PGRI Dlanggu during the PAI learning process, and 2) The use of learning videos as a medium to support PAI for these students. A qualitative approach with a case study method is used, collecting data through participatory observation, semistructured interviews, and documentation. Data analysis involves three stages: reduction, presentation, and conclusion drawing/verification. The study reveals that students' characteristics include: a) universal character traits, b) academic abilities, c) social/emotional aspects, and d) economic levels. The use of learning videos for PAI is supported by the Principal and Curriculum Coordinator as it is engaging and enhances learning motivation for students with disabilities, provided that teachers use it consistently.